Comparison between cone beam computed tomography and multislice computed tomography in diagnostic accuracy of maxillofacial fractures in dried human skull: an in vitro study. Issue 2 (4th July 2013) - Eskandarlou, Amir; Poorolajal, Jalal; Talaeipour, Ahmad Reza; Talebi, Sahar; Talaeipour, Maziar
Abstract Background The aim of this study was to compare the accuracy of cone beam computed tomography (CBCT) and multislice computed tomography (MSCT) in diagnosing factitious fractures in maxillofacial region as well as to investigate the influence of field of view (FOV) size on the interpretation of maxillofacial fractures in CBCT. Methods Simulated fractures were created in the right and left sides of five dried human skulls using a micro‐saw 20 mm blade without displacement. The skulls were scanned with a spiral 16‐slice MSCT scanner and a CBCT device with two FOVs (6 × 6, 15 × 15). Three observers assessed and interpreted the images judging whether fracture was present or absent. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and the area under the receiver operating characteristic (ROC) curve were calculated. Results The sensitivity of CBCT 6 × 6, CBCT 15 × 15, and MSCT was 87.5%, 70.7%, and 49.7% and the specificity of three modalities was 91.7%, 88.0%, and 98.3%, respectively. The area under ROC curve was 0.90 (95% CI: 0.85, 0.94) for CBCT with FOV 6 × 6, 0.79 (95% CI: 0.75, 0.85) for CBCT with FOV 15 × 15, and 0.74 (95% CI: 0.69, 0.79) for MSCT. The Kappa value for interobserver agreement was highest for CBCT 6 × 6 among imaging modalities. Conclusions CBCT with small FOV had higher diagnostic accuracy in detecting simulated maxillofacial fractures than MSCT. However, additional evidence based on in vivo studies is needed to confirm the superiority of CBCT on MSCT in diagnosis of maxillofacial traumatic fractures.